Aplicação da teoria do inadimplemento eficiente aos contratos nacionais - Perri, Cláudia Haidamus (2017)
This paper discusses the American theory of “efficient breach of contract”, long acclaimed by mentors of the “Law and Economics” movement. After a brief digression to recall the origins of Common Law and Civil Law in order to provide a clear view of the converging and diverging points between both systems, we will present our understanding about how the hybridization of such systems occurs in current Brazilian Law. We will then move on to the general theory of contracts under Brazilian law as applied to business contracts, that is, the general theory of contracts from a socioeconomic perspective. We will approach the dialog between the principles that govern civil and business relationships, with the aim of demonstrating that there are differences that should be taken into consideration in order to consolidate an economically strong, stable society that ensures a firm legal basis for contractual transactions. After showing how the American contract law system focuses on the economic objective of contracts, we will, by means of a comparative study, approach the consequences of breaches of contract (and the effects thereof) under both systems. Afterwards, we will explain the theory of efficient breach of contract, notably under American contract law, looking at a series of cultural impediments and jurists” opinions that hinder the path for its recognition in the courts and in the academic world within Civil Law jurisdictions, which are less inclined to accept the applicability and development of the “efficient breach of contract” principle than is the American law. By identifying and discussing such impediments and difficulties (based on other Civil Law jurisdictions where this topic has already been subjected to debate), we will try to demonstrate that the economists” views and the views of legal scholars specializing in comparative law are able to find common ground, interact, and accept this (highly polemic) theory in our country. The study of contract law under the light of the “Law and Economics” movement implies bringing under debate one more hermeneutical tool from amongst the many others that exist